Raw and Cooked Vegetable Consumption and Risk of Cardiovascular Disease: A Study of 400,000 Adults in UK Biobank - Feng, Qi; Kim, Jean H.; Omiyale, Wemimo; Bešević, Jelena; Conroy, Megan; May, Margaret; Yang, Zuyao; Wong, Samuel Yeung-shan; Tsoi, Kelvin Kam-fai; Allen, Naomi; Lacey, Ben (Frontiers in Nutrition, 2022)
Objectives: Higher levels of vegetable consumption have been associated with lower risk of cardiovascular disease (CVD), but the independent effect of raw and cooked vegetable consumption remains unclear. Methods: From the UK Biobank cohort, 399,586 participants without prior CVD were included in analysis. Raw and cooked vegetable intakes were measured with a validated dietary questionnaire at baseline. Multivariable Cox regression was used to estimate the associations between vegetable intake and CVD incidence and mortality, adjusted for socioeconomic status, health status and lifestyle factors. The potential effect of residual confounding was assessed by calculating the percentage reduction in the likelihood-ratio (LR) statistics after adjustment for the confounders. Results: The mean age was 56 years and 55% were women. Mean intakes of raw and cooked vegetables were 2.3 and 2.8 tablespoons/day, respectively. During 12 years of follow-up, 18,052 major CVD events and 4,406 CVD deaths occurred. Raw vegetable intake was inversely associated with both CVD incidence (adjusted hazard ratio (HR) [95%CI] for highest vs. lowest intake: 0.89 [0.83-0.95]) and CVD mortality (0.85 [0.74-0.97]), while cooked vegetable intake was not (1.00 [0.91-1.09] and 0.96 [0.80-1.13], respectively). Adjustment for potential confounders reduced the LR statistics for the associations of raw vegetables with CVD incidence and mortality by 82% and 87%, respectively. Conclusions: Higher intakes of raw, but not cooked, vegetables were associated with lower CVD risk. Residual confounding is likely to account for much, if not all, of the observed associations. This study suggests the need to reappraise the evidence on the burden of CVD disease attributable to low vegetable intake in high-income populations.